2020
DOI: 10.3329/ajmbr.v6i1.46482
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of climate change on livelihood of the fishersˊ at the Meghna, Laukhati and Galachipa river in Bangladesh

Abstract: Climate change is a global threat to the world especially for Bangladesh, due to its geographical location. The present study was carried out to the impacts of climate change on livelihood of the fishers at the Meghna, Laukhati and Galachipa river in Bangladesh. The study was assessing the effects of climate change on fishersˊ community in the Meghna, Laukhati and Galachipa rivers near Chandpur and Patuakhali districts. The data on fishersˊ livelihood were collected by using a well-developed questionnaire from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Ali et al (2009) found that about 42% of the fishers lived in nuclear family and rest 57.50% in the whole family in the district of Mymensingh. Rahaman et al (2020) found that most of the fishers were belonged to the age groups of 41 to 60 years (45%), represented by 75% muslim and joint family type (61%) was the predominant among the fishers. Human resource development and social advancement are dependent on the education.…”
Section: Demographic Information Of the Fishersmentioning
confidence: 98%
See 1 more Smart Citation
“…Ali et al (2009) found that about 42% of the fishers lived in nuclear family and rest 57.50% in the whole family in the district of Mymensingh. Rahaman et al (2020) found that most of the fishers were belonged to the age groups of 41 to 60 years (45%), represented by 75% muslim and joint family type (61%) was the predominant among the fishers. Human resource development and social advancement are dependent on the education.…”
Section: Demographic Information Of the Fishersmentioning
confidence: 98%
“…Table 6 represents major problems and constraints faced by the fishers in the present study. Additionally, Islam et al (2020), Rahaman et al (2019) and Hossain et al (2018) found that the catch per unit effort of fishersˊ nets was declined due to decreased species composition. Sufian et al (2017) investigated the major problems and constraints associated with fishing and livelihood in Dekar haor of Sunamganj in Bangladesh.…”
Section: Major Problems and Constraints Associated With Fishing And Lmentioning
confidence: 99%
“…Ahmed et al [29] recorded that dissolved oxygen contents in their experimental ponds ranged from 5.5 to 18 mg/l. Halim et al [14] recorded dissolved oxygen ranged from 1.2 to 8.5 mg/l Hossain [4] recorded DO values of fish ponds ranging from 3.8 to 6.9 mg/l and 2.04 to 7.5 mg/l respectively at Mymensingh region. From the above discussion, it may be concluded that the oxygen content of the experimental ponds were within the good productive range.…”
Section: Dissolved Oxygen (Mg/l)mentioning
confidence: 99%
“…Fisheries play a vital role in nutrition, livelihood earning and export earnings in Bangladesh. Fishes contribute to 60% of animal protein intake, about 4.39% of gross domestic product and 2.46% of export earnings; approximately 1.4 million people are directly engaged in fishing, 11 million in part-time fishing and another 3 million in aquaculture activities [1][2][3][4]. However, the International Union for Conservation of Nature (IUCN), Bangladesh [5] assessed 253 freshwater fish species and revealed 64 as threatened species in Bangladesh, of which 9 were critically endangered, 30 were endangered, 25 were vulnerable, near threatened 27, least concern 122 and 40 data deficient freshwater species [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation